Tulta päin! Piirteitä sotilaallisesta ajattelusta ranskassa ennen ensimmäistä maailmansotaa - Jouko, Petteri (Tiede ja ase, 2017)
A war of attrition ravaged along the French northern border a century ago. The nature of war and battle were something totally different from the pre-war ideas promoting speed, bold movement and manoeuvre. The concept of an attack where the superior morale of the troops makes up for deficiencies in equipment had matured into a tactical doctrine which was integrated into the war plans in the decade preceding the Great War. The doctrine failed mainly due to the amount of firepower of used by the opposing sides. What followed was an operational and mental stalemate that lasted for almost four years. This article is focused mainly on the French strategic and tactical thinking before the war. Who were the French thinkers, and how did they see and predict the nature of war and battle? The tactical doctrine can be seen in the family of contemporary regulations and manuals but ideas behind the text are harder to assess. The writings of contemporary thinkers – including influential commanders such as Henri Bonnal or Ferdinand Foch – provide some background for the manuals. The article offers a description of the French way of thinking rather than an analysis. The latter is impossible and, therefore, also useless without profound knowledge of the era. However, the French thinking promoted a Napoleonic strategy seeking a decisive battle or a series of battles of annihilation. Rapid offensive manoeuvre was a precondition for the concentration of forces at a decisive point. Speed, in turn, was interlinked with surprise and initiative which were vital to the numerically inferior party. Moreover, in order to achieve a sound strategic setting, tactics were founded on rapid and straightforward action promoting moral superiority against the enemy.